Strategy to Construct Stair‐Shaped Partially Reduced Naphtho[1, 2‐b]pyrano[2, 3‐d]oxepines and Dinaphtho[1, 2‐b, d]oxepines. (16th September 2016) - Gautam, Sanjay K.; Maurya, Hardesh K.; Pratap, Ramendra; Kumar, Brijesh; Kumar, Abhinav; Tandon, Vishnu K.; Ram, Vishnu Ji
Abstract : A concise and efficient base‐induced synthesis of stair‐shaped, 4‐methylthio‐2‐oxo‐5, 6‐dihydro‐2 H ‐naphtho[1, 2‐b]pyran[2, 3‐ d ]oxepine‐3‐carbonitriles (3 ) has been delineated by the reaction of 3, 4‐dihydronaphtho[1, 2‐b]oxepin‐5(2 H )‐one (1 ) and methyl 2‐cyano‐3, 3‐dimethylthioacrylate in DMSO using powdered KOH as a base at room temperature.Amination of3 has been achieved by reaction with secondary amine in ethanol at reflux temperature to yield 4‐ sec ‐amino‐2‐oxo‐5, 6‐dihydro‐2 H ‐naphtho[1, 2‐ b ]pyran[2, 3‐ d ]oxepine‐3‐carbonitriles (4 ). Reaction of3 with aryl methyl ketone (5 ) in DMSO at room temperature using powdered KOH as a base produced stair‐shaped 5‐aryl‐7, 8‐dihydro‐1, 4‐dioxa‐2, 3‐dioxodinaphtho[1, 2‐ b, d ]oxepine (6 ) in good yields. However, reaction of 6‐aryl‐2 H ‐pyran‐2‐one‐3‐carbonitrile (8 ) with 3, 4‐dihydronaphtho[1, 2‐ b ]oxepin‐5(2 H )‐one (1 ) did not give similar product, but in lieu 4‐aryl‐5, 6‐dihydronaphtho[1, 2‐ b ]oxepino[4, 5‐ b ]pyran‐2‐ylidene)acetonitrile (9 ) was isolated and characterized. Abstract :